Lymphoma and Leukemia of the Nervous System - Batchelor, Tracy.; Batchelor, Tracy.; DeAngelis, Lisa M.; DeAngelis, Lisa M. (Springer New York : Imprint: Springer, 2012)
Lymphomas and leukemias of the nervous system result in devastating neurological complications and high mortality. These malignancies may arise within the central nervous system or may disseminate to the brain or cerebrospinal fluid from a source elsewhere in the body. Early diagnosis and therapeutic intervention lead to improvement in neurological symptoms and signs and potentially improved survival. The diagnostic evaluation and treatment of lymphoma and leukemia of the nervous system differ from the standard approaches used when the disease is confined outside of the nervous system. Lymphoma and Leukemia of the Nervous System is a comprehensive review of this challenging group of diseases and should be useful for the practicing neurologist, hematologist, oncologist and for any practitioner involved in the management of these patients.   Review of the first edition   This book, the first devoted primarily to the disease (Primary CNS Lymphoma), provides a comprehensive source for the study of the clinical features, diagnostic aspects, and approaches of lymphoma treatment. Although the main focus of the book is primary central nervous system lymphoma, several contributing authors also provide high-quality chapters on the neurologic manifestations of non-Hodgkin's lymphoma, Hodgkin's disease, and plasma-cell disorders and the neurologic complications of lymphoma therapy. This book — up-to-date, concise, and clearly written — provides a review of the disease that is more in-depth than that found even in subspecialty textbooks.   Joachim Yahalom, M.D., Department of Radiation Oncology Memorial Sloan-Kettering Cancer Center New England Journal of Medicine.